PERTANGGUNGJAWABAN PIDANA PELAKU TUKAR PASANGAN (SWINGER) BERDASARKAN PASAL 296 KUHP - Saputra, Reza Aditya; Solihin, Uu Idjudin; Fathammubina, Rohendra (Peneliti.net, 2024)
Decency crime is the most ancient form of crime in the history of human civilization. Within the scope of marriage, this crime can still occur, for example, the crime of swapping partners. In this case, the crime of partner exchange is committed by several married couples who like to exchange partners in sexual relations. This study aims to determine the application of the law to the act of exchanging spouses (swinger) based on Article 296 of the Criminal Code concerning Obscene Acts, examining what factors are the causes of the crime of partner exchange (swinger) and examining the criminal liability of the swinger. in Article 296 of the Criminal Code concerning Obscene Acts. This study uses a normative juridical research method where the main material uses legal materials by examining theories, concepts, legal principles and legislation related to this research. This research is commonly referred to as a literature study, which examines statutory regulations, law books, and other documents to support this research. From the results of the research and discussion, it can be concluded that the action of the couple's tukkar has fulfilled the elements in Article 296 of the Criminal Code because the perpetrator who committed the act has resulted in obscene acts for others.